Basic psychological needs and GRIT in Peruvian university students - Marcelo-Torres, Nohemi; Manyari-Masias, Maria Pia; Calderón-Sánchez, Raymundo; Tutte, Veronica; Brandão, Regina; Caycho-Rodríguez, Tomás; Reyes-Bossio, Mario (Frontiers in Education, 2024)
The present quantitative study of predictive design aims to determine the influence of basic psychological needs and some socio-demographic variables on GRIT, in a sample constituted by scholarship students financed by (PRONABEC) from a private university in Lima. The GRIT Scale and Basic Psychological Need Satisfaction and Frustration Scale were applied to 865 students, 54.7% were female, the ages fluctuated between 16 and 47 years of age, 74.5% were residents in Lime. Results demonstrated that Basic Psychological Need's satisfaction has a positive influence on GRIT. On the other hand, there is a negative relationship between the GRIT dimensions (consistency and perseverance) and BPN frustration. In addition, women and first generation students showing higher GRIT levels. To conclude, this research confirms a high degree of influence of the competence needs satisfaction dimension on the GRIT and the influence of sociodemographic variables in achieving objectives.